Komparatystyczne studium historycznych i współczesnych metod oraz kryteriów oceny wiarygodności dokumentów = A comparative study of historical and contemporary methods as well as criteria used for the assessment of the authenticity of documents - Streit, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A significant position of documents in social, political and economic life entails a need to improve methods of verifying documents' authenticity; in the case of historical documents it is connected with cognitive purposes of an academic whereas in the case of contemporary documents it is necessary to provide reliability of documents' circulation.
Keywords: czasopismo akademickie; polityka; kultura; czasopismo